1999
DOI: 10.1038/8811
|View full text |Cite
|
Sign up to set email alerts
|

c-MYC interacts with INI1/hSNF5 and requires the SWI/SNF complex for transactivation function

Abstract: Chromatin organization plays a key role in the regulation of gene expression. The evolutionarily conserved SWI/SNF complex is one of several multiprotein complexes that activate transcription by remodelling chromatin in an ATP-dependent manner. SWI2/SNF2 is an ATPase whose homologues, BRG1 and hBRM, mediate cell-cycle arrest; the SNF5 homologue, INI1/hSNF5, appears to be a tumour suppressor. A search for INI1-interacting proteins using the two-hybrid system led to the isolation of c-MYC, a transactivator. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
278
2
5

Year Published

2000
2000
2014
2014

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 347 publications
(296 citation statements)
references
References 22 publications
9
278
2
5
Order By: Relevance
“…These consist of two imperfect repeats, Rpt1 and Rpt2 and an c-terminal putative coiled coil domain (Morozov et al, 1998). Rpt1 is required for interaction with cmyc (Cheng et al, 1999). The c-terminal coiled coil domain is likely to be involved in protein-protein interactions yet to be specified.…”
Section: Resultsmentioning
confidence: 99%
“…These consist of two imperfect repeats, Rpt1 and Rpt2 and an c-terminal putative coiled coil domain (Morozov et al, 1998). Rpt1 is required for interaction with cmyc (Cheng et al, 1999). The c-terminal coiled coil domain is likely to be involved in protein-protein interactions yet to be specified.…”
Section: Resultsmentioning
confidence: 99%
“…The functional relationship of MYC with BRG1 and with the SWI/SNF complex is well established. For example, MYC physically interacts with the SWI/ SNF component, SMARCB1 ( 26 ), and BRG1 is required to regulate the expression of MYC and MYC target genes ( 16 , 27 ). In tumors carrying BRG1 mutations, this regulation is abolished, thereby preventing cell differentiation and promoting cell growth ( 16 ).…”
Section: Discussionmentioning
confidence: 99%
“…15 Alternatively, RSF-1 overexpression may directly contribute to tumor invasiveness and metastasis. In fact, recent studies have indicated that certain proteins contributing to metastasis, such as metastasis-associated gene in NuRD complex 25 or MYC and BRCA1 in SWI/SNF complex, 26,27 can form functional complexes with chromatin remodeling factors in promoting cancer progression.…”
Section: Discussionmentioning
confidence: 99%